Pengaruh Pola Asuh Orang Tua Dan Ikatan Emosional Teman Sebaya Terhadap Motivasi Beribadah Peserta Didik Di Smp Negeri 6 Malang - M. Fiqih Anas Rifqi Abqoriya (EDUTHINK: Jurnal Pemikiran Pendidikan Islam, 2022)
Prayer is one of the Islamic Shari'a that must be carried out by every Muslim, especially children in school. Many things affect the worship of prayer on students, the feeling of laziness from the students themselves is the dominant factor in the desire to carry out it. Unfavorable peers are also a factor in preventing them from praying. Not to mention if students at home do not have the attention of their parents to motivate them to pray, of course at school students will be lazy to do it. The purpose of this study was to determine whether there is an influence between parenting patterns and the emotional bonds of peers on the motivation of students to worship. This research includes quantitative research. The population and samples were taken from students of SMPN 6 Malang, totaling 798 students with a sample of 160 students using random sampling. The data analysis method uses Multiple Regression Analysis with a questionnaire as the main data collection method, The results of this study indicate that there is no relationship between the influence of parenting patterns on the worship motivation of students at SMPN 6 Malang. This is evidenced by the regression coefficient number -192 and obtained a significance value of 0.848. This figure shows that the category of statistical significance test is greater than 0.05. The variable of peer emotional bonding on students' motivation to worship, shows an influence as evidenced by the results of hypothesis testing having a regression coefficient of 0.8.188 and a significance value of 0.000 is obtained. The statistical value of the significance test is smaller than 0.05.